Solve for \( n \) \[ \begin{array}{c}6 n-7(n+1)=6 n \\ n=\square \\ \text { Submit }\end{array} \]
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve for \( n \), we start with the equation: \[ 6n - 7(n + 1) = 6n \] First, distribute the \(-7\) on the left-hand side: \[ 6n - 7n - 7 = 6n \] Now, combine like terms: \[ - n - 7 = 6n \] Next, add \( n \) to both sides to get all terms involving \( n \) on one side: \[ - 7 = 6n + n \] This simplifies to: \[ - 7 = 7n \] Now, divide both sides by \( 7 \): \[ n = -1 \] Thus, the solution is: \[ n = -1 \]